Kandungan IAA, serapan hara, pertumbuhan dan produksi jagung dan kacang tanah sebagai respon terhadap aplikasi pupuk hayati - Sigit Tri Wibowo; . Hamim; Aris Tri Wahyudi (Institut Pertanian Bogor, 2009)
The aim of this research was to study IAA content, nutrient uptake, growth and productivity of maize and peanut in response to application of biofertilizer. The research was conducted in a green house of Cikabayan IPB Farm, Bogor Agriculture University, Darmaga, Bogor, West Java. A completely randomized design was applied in single factor experiment for maize and peanut with 3 replications. The treatments consisted of 4 factors: I. Without fertilizer, II. 100% biofertilizer (dosage 100g/pot), III. 100% inorganic fertilizer, and IV. Combination of biofertilizer and inorganic fertilizer with 50% dosage. Biofertilizer was applied using compost enriched by Pseudomonas sp., Bacillus sp., Azotobacter sp., Azospirillum sp., Rhizobium sp, and P-solubilising bacteria. The dosage of inorganic fertilizer was 0.5 gfpot of Urea; 0.5 g/pot of SP-36; 0.375 g/pot of KCI for maize, and 0.125 g/pot of Urea; 0.5 g/pot of SP-36; 0.375 g/pot of KCI for peanut. Application of biofertilizer enhanced auxin content of maize by 73-159°/o, but not in peanut. The treatment also increased the uptake of N, P, and K of both plants by 2 to 35 times as compared to control plant. The production increased by 270% on maize and 66% on peanut due to application of biofertilizer. The result showed that application of compost enriched by microbial activator was able to supplement inorganic fertilizer for growth and production of maize and peanut.